ANALISIS PERFORMA KOLEKTOR SURYA PELAT DATAR DENGAN SIRIP MELINTANG BERONGGA DISUSUN STAGGERED MENGGUNAKAN ALIRAN IMPINGING JET - Purnama, Hunafa Arya; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract The majority of Indonesians work in the agricultural sector as Indonesia is an agrarian country that has the advantage of fertile land. In this sector, one of the most ancient and frequently used drying methods is direct drying. However, this method has disadvantages, such as the need for large areas of land, inconsistent drying results due to varying solar radiation intensity, as well as the risk of contamination from microorganisms, dust, and dirt. These conditions encourage humans to look for more efficient ways of utilizing solar energy for drying, such as the use of solar collectors. A solar collector device has the ability to absorb heat energy from sunlight and flow it into the working fluid. This experiment was conducted to observe the heat transfer that occurs inside the solar collector. To improve the performance of the solar collector, hollow transverse fins in the shape of a square are arranged staggeredusing impinging jet flow with a mass flow rate variation of 0.0009 (?1); 0.0019 (?2); and 0.0023 (?3) kg/s at a temperature of 32 ?C. The results showed that in the solar collector, there was the highest temperature distribution and useful energy in the variation of (?3) with useful energy of 39.44 W and the highest efficiency in the variation of (?2) of 14.40%. But the average useful energy and average efficiency were at kg/s variation (?3) of 26.53 W and 5.69%. This shows that the variation of mass flow rate affects the performance of the solar collector. Keywords: Solar Energy, Staggered,Impinging jet, Hollow Fin, Useful Energy, Efficiency.